College academic identities situated in interlocking contextual blocks. Issue 4 (4th July 2018) - Oikonomidoy, Eleni
ABSTRACT: Through an examination of 13 first-generation college students' views, this paper aims to provide one possible lens to viewing the complex social and academic landscapes that impact on students' academic identity construction. Academic and social experiences within and beyond the safety net of a mentoring program are explored. The paper concludes with recommendations for campus-wide initiatives for the support of the focal students.